2017
DOI: 10.4172/2329-8863.1000295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Quality and Deficit Irrigation on Tomatoes Yield and Quality: A Review

Abstract: Tomato is one of the vegetable crops of worldwide demand because of its various purposes including nutritional and medicinal values. It produced in Ethiopia largely for domestic consumption by small scale farmers and private producers. Tomato production and productivity affected by biotic and abiotic factors. Water quality and deficit irrigation has been considered as factor in its production, yield and quality as reported by many authors worldwide. Salinity, toxicity of heavy metals, temperature, microorganis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…where s -seasonality, Ω The results of the water quality analysis have shown that the main problems in the Ingulets irrigation system are high total dissoluble salts (TDS), toxic ions (eCl -) and sodium content: 1489-2280 mg/L, 10.49-21.63 me/L and 11.83-21.97 me/L respectively. Irrigation with such water leads to deterioration of the physical, chemical and biological properties of soils, decrease in crops growth, productivity and yield quality (Wilcox, 1955;Kelly, 1963;Ayers and Westcott, 1985;Ould Ahmed et al, 2007;Feizi et al, 2010;Lozovitsii, 2012;Kim et al, 2016;Banjaw et al, 2017;Lykhovyd and Lavrenko, 2017). The statistical data processing has also shown that the most variable quality criteria in the Ingulets irrigation system water are chloride and sodium ions content (CV was 42.76% and 25.84% respectively), and the most stable one was power of hydrogen (pH) with CV at 8.39%.…”
Section: Methodsmentioning
confidence: 99%
“…where s -seasonality, Ω The results of the water quality analysis have shown that the main problems in the Ingulets irrigation system are high total dissoluble salts (TDS), toxic ions (eCl -) and sodium content: 1489-2280 mg/L, 10.49-21.63 me/L and 11.83-21.97 me/L respectively. Irrigation with such water leads to deterioration of the physical, chemical and biological properties of soils, decrease in crops growth, productivity and yield quality (Wilcox, 1955;Kelly, 1963;Ayers and Westcott, 1985;Ould Ahmed et al, 2007;Feizi et al, 2010;Lozovitsii, 2012;Kim et al, 2016;Banjaw et al, 2017;Lykhovyd and Lavrenko, 2017). The statistical data processing has also shown that the most variable quality criteria in the Ingulets irrigation system water are chloride and sodium ions content (CV was 42.76% and 25.84% respectively), and the most stable one was power of hydrogen (pH) with CV at 8.39%.…”
Section: Methodsmentioning
confidence: 99%